PENERAPAN PENILAIAN AUTENTIK KURIKULUM 2013 PADA DOMAIN SIKAP UNTUK MATA PELAJARAN PAI DAN BUDI PEKERTI DI SMA NEGERI 1 ASEMBAGUS - Abd Aziz; Subyanto Subyanto (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2019)
Many teachers only pay attention to cognitive and psychomotor development and override affective domain of the students, but that did not happen at SMA Negeri 1 Asembagus (State Senior High School 1 Asembagus. Authentic assessment in Kurikulum 2013 (2013 curriculum) has been conducted for attitude assessment on Islamic education subject and character education subject at at SMA Negeri 1 Asembagus (State Senior High School 1 Asembagus). This research is descriptivequalitative research by data collection techniques in the form of observation, interviews, and documentation, then analyzing data in this research using data reduction, data presentation, and verification. Triangulation is done for checking validity of data. The results of this study are the implementation of authentic assessment through four stages involves determining basic competence, determining object, determing assessment technique, and assessment enforcement, both in the classroom or outside the classroom.